The role of weight bias and role-modeling in medical students' patient-centered communication with higher weight standardized patients. Issue 8 (August 2021) - Phelan, Sean M.; Puhl, Rebecca M.; Burgess, Diana J.; Natt, Neena; Mundi, Manpreet; Miller, Nathaniel E.; Saha, Somnath; Fischer, Kristin; van Ryn, Michelle
Highlights: Perceiving weight bias as normative for physicians was associated with less friendliness, attentiveness, respectfulness and interactivity. Self-reported frequency of faculty role-modeling of discrimination against patients with obesity was also associated with less patient-centered behavior. Implicit weight bias was not associated with any measure of patient-centered communication. Abstract: Objective: Patients with obesity may experience less patient-centered care. We assessed whether medical students' implicit/explicit weight-related attitudes and perceptions of normative attitudes are associated with patient-centered care for patients with obesity. Methods: Third and fourth year medical students (N = 111) at one medical school completed a survey and participated in a patient care scenario with a standardized patient with obesity. Encounters were coded for patient-centered behavior. Predictors of patient-centered behaviors were assessed. Results: Student perceptions that negative attitudes about patients with obesity are normative in medical school were significantly associated with poorer patient-centered behaviors, including lower attentiveness (b=−0.19, p = 0.01), friendliness (b=−0.28, p < 0.001), responsiveness (b=−0.21, p = 0.002), respectfulness (b=−0.17, p = 0.003), interactivity (b=−0.22, p = 0.003), likelihood of being recommended by observers (b=−0.34, p < 0.001), and patient-centeredness index scores (b=−0.16, p = 0.002). Student reported faculty role-modeling of discrimination against patients with obesity predicted lower friendliness (b=−0.16, p = 0.03), recommendation likelihood (b=−0.22, p = 0.04), and patient-centeredness index score (b=−0.12, p = 0.03). Conclusions: Negative normative attitudes and behaviors regarding obesity in the medical school environment may adversely influence the quality of patient-centered behaviors provided to patients with obesity. Practice implications: Efforts to improve patient-centered communication quality among medical trainees may benefit from intervention to improve group normative attitudes about patients with obesity.